CHEMICAL AND PHYSICAL PROPERTIES OF UPGRADED BROWN COAL - DATIN F. UMAR; HIROMOTO USUI; BUKIN DAULAY; IWAN RIJWAN; IKIN SODIKIN (Puslitbang tekMIRA, 2006)
Results of proximate analyses indicate that inherent moisture of the upgraded coals decrease signifi- cantly compared to that of the raw coals. Hence, the calorific value of the upgraded coals increases. The ash content of the upgraded coals did not change obviously due to the UBC process which was conducted at low temperature. However, the volatile matter content increase slightly due to the residue plugs over coal pores to prevent re-absorb of moisture. From ultimate analyses, carbon content of the upgraded coals increases, whereas the hydrogen and oxygen contents decrease. The UBC process hardly effects to the sulfur and nitrogen contents. The equilibrium moisture of the upgraded coals was determined by using ASTM Standard method, most of them were less than 9%. The functional group of C-H and C=O of the upgraded coals were slightly less than that of the raw coals. The aromaticity of coal, all of the upgraded coals was increase. The petrography of both the raw and the upgraded coals indicates that the mean vitrinite reflectance was slightly higher in the upgraded coal compared to that of the raw coal. There was no significant quantity and textural differences of maceral in both coals. The specific surface area of the upgraded coals was lower than that of the raw coals due to the plugging of pore structure and shrinkage by residual oil addition. The briquettability of Upgraded coal briquette according to drop shatter test and compressive strength indicates good characteristics of briquette.